Decreased Regulatory T Cells in Vulnerable Atherosclerotic Lesions: Imbalance between Pro- and Anti-Inflammatory Cells in Atherosclerosis - Ilonka Rohm; Yevgeniya Atiskova; Stefanie Drobnik; Michael Fritzenwanger; Daniel Kretzschmar; Rudin Pistulli; Jürgen Zanow; Thomas Krönert; Gita Mall; Hans Reiner Figulla; Atilla Yilmaz (Mediators of Inflammation)
Atherosclerosis is a chronic inflammatory disease of the arterial wall in which presentation of autoantigens by dendritic cells (DCs) leads to the activation of T cells. Anti-inflammatory cells like Tregs counterbalance inflammation in atherogenesis. In our study, human carotid plaque specimens were classified as stable (14) and unstable (15) according to established morphological criteria. Vessel specimens (n=12) without any signs of atherosclerosis were used as controls. Immunohistochemical staining was performed to detect different types of DCs (S100, fascin, CD83, CD209, CD304, and CD123), proinflammatory T cells (CD3, CD4, CD8, and CD161), and anti-inflammatory Tregs (FoxP3). The following results were observed: in unstable lesions, significantly higher numbers of proinflammatory cells like DCs, T helper cells, cytotoxic T cells, and natural killer cells were detected compared to stable plaques. Additionally, there was a significantly higher expression of HLA-DR and more T cell activation (CD25, CD69) in unstable lesions. On the contrary, unstable lesions contained significantly lower numbers of Tregs. Furthermore, a significant inverse correlation between myeloid DCs and Tregs was shown. These data suggest an increased inflammatory state in vulnerable plaques resulting from an imbalance of the frequency of local pro- and anti-inflammatory immune cells.